Acoustic barrier simulation of construction and demolition waste: A sustainable approach to the control of environmental noise. (November 2021) - Amarilla, Rosemara Santos Deniz; Scoczynski Ribeiro, Rodrigo; Henrique de Avelar Gomes, Márcio; Pereira Sousa, Raylton; Henrique Sant'Ana, Luis; Eduardo Catai, Rodrigo
Abstract: The use of construction waste to build noise barriers is a considerable reason in determining sustainability and environmental noise control. The present study aims to analyze the sound absorption coefficient of concrete blocks from construction and demolition waste (CDW), to apply in computer simulation of noise barrier in urban area. Thus, the research presents a double environmental aspect, on the one hand, the reduction of sound pressure levels from road traffic noise and, on the other hand, the recycling of construction by-products. The sound absorption coefficient was characterized by normal incidence. To obtain the attenuation behavior of the barrier, the new sound absorption coefficient of the material was inserted in the SoundPlan database, acoustic prediction software. The results showed that the insertion of a simple barrier from construction and demolition waste (CDW) is advisable to reduce noise outdoors. As for concrete blocks from CDW for the building of noise barriers can become a sustainable alternative, mitigating the sound impact and/or the environmental impact. Current trends are oriented towards finding alternative sustainable materials for concrete, one example is the recycling of waste from construction by-products.